The Crime of Genocide on the Rohingya Ethnic in Myanmar from the Perspective of International Law and Human Rights - Nasution, Aulia Rosa (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
AbstractGenocide has become one of the most essential issue nowadays in the world since the ethnic conflict on Rohingya occurred in Myanmar. This conflict which has killed thousands of innocence civilians happened over the last century and increasingly heating up in the 21st century. Genocide on the Rohingya constitute a serious international crime which was conducted widespread and systematically, carried out by state actors (state agents or military apparatus) and non- state actors by destruction in whole or in part. This research focuses on the crime of genocide that occurred in the conflict of Rohingya which reviewed based on aspects of international law and human rights. The research results show that genocide on the Rohingya Ethnic has become a crime against humanity and violates the principle of humanity.Abstrak Genosida saat ini menjadi salah satu persoalan yang paling penting di dunia sejak terjadinya insiden konflik sejak konflik etnis Rohingya terjadi di Myanmar. Konflik ini telah membunuh ribuan orang â orang sipil yang tidak bersalah yang terjadi selama berabad-abad yang lalu dan semakin memanas di abad ke-21. Genosida pada etnis Rohingya merupakan kejahatan internasional yang serius yang dilakukan secara meluas dan sistematik, dilakukan oleh aktor-aktor negara (agen-agen negara atau aparat militer) dan aktor-aktor non negara dengan penghancuran secara sebagian atau keseluruhan. Penelitian ini berfokus pada kejahatan genosida yang terjadi pada konflik etnis Rohingya yang dikaji melalui aspek- aspek hukum internasional dan hak asasi manusia. Penelitian ini menunjukkan bahwa genosida pada etnis Rohingya merupakan kejahatan terhadap kemanusiaan dan melanggar prinsip- prinsip kemanusiaan.DOI: https://doi.org/10.22304/pjih.v5n1.a10